Influence of the polysaccharide capsule on virulence and fitness of Klebsiella pneumoniae - Zierke, Lisa; Mourad, Rodi; Kohler, Thomas P.; Müsken, Mathias; Hammerschmidt, Sven (Frontiers in Microbiology, 2025)
IntroductionThe capsular polysaccharide (CPS) of pathogenic bacteria is a critical virulence factor, often evading phagocytosis by host immune cells, while also interfering with the contact of the pathogen with host cells and contributing to biofilm formation. Klebsiella pneumoniae, a Gram-negative human pathogen associated with high antimicrobial resistances, produces 77 CPS serotypes. The CPS masks proteinaceous factors but also protects K. pneumoniae from uptake by host phagocytic cells and activation of the complement system. In addition to nosocomial, urinary tract and bloodstream infections or pneumonia hypervirulent strains have a highly mucoid phenotype and can cause soft tissue infections, liver abscesses, and meningitis as well. The CPS is therefore crucial for both escaping detection by the immune system and enhancing the virulence potential.MethodsIn this study, we generated a non-encapsulated mutant (Kpn2146∆wza) to observe how the CPS interferes with K. pneumoniae adhesion, survival in blood, and invasiveness in an experimental infection model.ResultsInfection of A549 lung epithelial cells showed similar adherence levels for the wild-type and non-capsulated strain, while our data showed a moderately higher internalization of Kpn2146Δwza when compared to the wild-type. In whole blood killing assays, we demonstrate that the K. pneumoniae capsule is essential for survival in human blood, protecting K. pneumoniae against recognition and clearance by the human immune system, as well as complement-mediated opsonization and killing. The non-encapsulated mutant, in contrast, was unable to survive in either whole blood or human plasma. Infections of Galleria mellonella larvae showed a significantly decreased virulence potential of the CPS-deficient mutant.DiscussionIn conclusion, our data indicate a crucial role of CPS in vivo.